Protein Topology Prediction Algorithms Systematically Investigated in the Yeast Saccharomyces cerevisiae. (11th July 2019) - Weill, Uri; Cohen, Nir; Fadel, Amir; Ben‐Dor, Shifra; Schuldiner, Maya
Abstract : Membrane proteins perform a variety of functions, all crucially dependent on their orientation in the membrane. However, neither the exact number of transmembrane domains (TMDs) nor the topology of most proteins have been experimentally determined. Due to this, most scientists rely primarily on prediction algorithms to determine topology and TMD assignments. Since these can give contradictory results, single‐algorithm‐based predictions are unreliable. To map the extent of potential misanalysis, the predictions of nine algorithms on the yeast proteome are compared and it is found that they have little agreement when predicting TMD number and termini orientation. To view all predictions in parallel, a webpage called TopologYeast:http://www.weizmann.ac.il/molgen/TopologYeast was created. Each algorithm is compared with experimental data and a poor agreement is found. The analysis suggests that more systematic data on protein topology are required to increase the training sets for prediction algorithms and to have accurate knowledge of membrane protein topology. Abstract : The predictions of nine algorithms on the yeast proteome are compared and it is found that they have little agreement when predicting transmembrane domain number and termini orientation. To view all predictions in parallel a webpage called TopologYeast was created.